Morfologia polínica, fenologia reprodutiva e biologia floral de espécies florestais de poaceae - Dórea, Marcos da Costa (2011)
Poaceae is traditionally known to exhibit homogeneous pollen grains. However, most of the studies available address grassland species with few representatives of forest, which include groups whose assisted pollination by insects contrast with the traditional anemophily identified for the family. This survey aimed to increase the pollen sampling of forest Poaceae species, with emphasis on Neotropical groups, with analyses of ektexine using SEM. None of the 86 analyzed samples, belonging to four subfamilies and seven tribes, had ektexine without ornamentation as expected for anemophilous pollen. Five patterns were described: areolate-microechinate (found in all tribes, except in Streptochaeteae, a total of 57 spp.); microechinate (Bambuseae, Olyreae and Streptochaeteae, with 12 spp.); and the others (areolate: 7 spp.; microechinate-perforate: 7 spp.; and microrugulate: 3 spp.) were restricted to Olyreae, a tribe of herbaceous bamboos almost exclusive of Neotropical forests, with species typical of the interior of them. The information presented here extends significantly the knowledge about palynological aspects of Poaceae species that occur in forests, due to 13 genera and 74 species had the ektexine patterns characterized for the first time. Furthermore, the interesting patterns of variation observed in subfamilies Anomochlooideae and Bambusoideae include differences among the tribes and within some genera, with potential applications for evolutionary studies in the group. In these two subfamilies, some ektexine patterns agree with the inflorescence morphology, which have some relations with pollination biology in these groups.